The effect of lipid and oxygen concentration on myosin heavy chain isoform expression in c2c12 and cultured Weddell seal (Leptonychotes weddellii) skeletal muscle cells - Garcia, Teresa Maria, author; Kanatous, Shane, advisor; Hamilton, Karyn, committee member; Mykles, Don, committee member (Colorado State University. Libraries, 2014)
The Weddell seal (Leptonychotes weddellii), a diving mammal, has large stores of myoglobin as compared to terrestrial mammals. Understanding the regulation of myoglobin in this unique species has therapeutic potential in people at risk of muscle infarction; to pursue this end, we established a successful protocol for the isolation and culture of primary Weddell seal skeletal muscle cells utilizing lipid-supplemented culture media. Using these cells, a study was designed to determine if increasing lipid in the media in either normoxic or hypoxic conditions would affect the expression of myosin heavy chain (MHC), which might explain a previously observed increase in myoglobin expression with increased lipid. Gel electrophoresis consistently resolved two putative MHC isoforms from seal and c2c12 cells. LC-MS/MS determined that the resolved bands were heterogeneous, and that all bands contained minimal adult MHC (10% or less, as measured by NSAF). Despite the minimal expression of adult MHC isoforms, myoglobin was detected in each treatment group. This study suggests that electrophoresis methods alone may not be sufficient to detect changes in MHC isoform abundance in cell culture, and that, in cell culture, regulatory pathways may exist for myoglobin that are independent of adult fiber type.
Keywords: fiber type; lipid; myoblast; myoglobin; primary cell culture; Weddell seal